Lactate-related lncRNAs assessment model predicts the prognosis of pancreatic ductal adenocarcinoma - Jing Sun; Tao Zhang; Shuai Zhu (Scientific Reports)
Abstract Accumulative lactate acid is a critical feature of pancreatic ductal adenocarcinoma (PDAC). Increasing evidence has demonstrated a close correlation between long non-coding RNAs (lncRNAs) and the survival of patients with PDAC. Nevertheless, research on the prognostic value of lactate-related lncRNAs in PDAC remains limited. In this study, the lactate-related lncRNAs were characterized based on their association with hypoxia-related genes in TCGA and StarBase database. Specifically, the dysregulated lactate-related lncRNAs in PDAC were identified as LA-DElncRNAs. Four LA-DElncRNAs were selected to develop clinical model, which demonstrated strong performance in survival prediction. The risk score derived from the model was identified as an independent prognostic factor for PDAC. Importantly, patients in the low-risk groups displayed more favorable prognoses compared to those in the high-risk groups. Moreover, patients with different risk scores showed distinct immune subtypes and variations in the levels of immune checkpoints. FAM225B was the most significant LA-DElncRNA associated with prognosis in Cox analysis, and the biological role of FAM225B was investigated both in vitro and in vivo. Knockdown of FAM225B, a significant LA-DElncRNAs, attenuated the proliferation and invasion of PDAC cells. In conclusion, the assessment model based on LA-DElncRNAs holds promise as a potential prognostic biomarker of PDAC patients. The identified four LA-DElncRNAs could help unravel the mechanisms underlying pancreatic tumorigenesis and identify novel molecular targets for treatment.